Factors influencing employees participation in intergenerational knowledge transfer within oil and gas community / Nur’syamimi Asyhikin Nazri - Nazri, Nur’syamimi Asyhikin (Faculty of Business and Management, 2018)
This study examines on the organizational factors influencing employees’ participation in intergenerational knowledge transfer within oil and gas community in Malaysia. This study consists of one dependent variable which is Intergenerational Knowledge Transfer and three independent variables which are Perceived Intergenerational Supportive Climate, Perceived Top Management Support and Perceived Organizational Institution Support. The study also involves a problem of employees participation in intergenerational knowledge transfer. The global population is ageing and the shrinking pool of of skillful and experience workforce will become a problem to the organization to sustain the organization’s knowledge asset. Hence, the three organizational factor were being tested whether it have significant effect with the employees participation in intergenerational knowledge transfer. The results were collected from 122 respondents through a questionnaire. A survey consisted of 30 questions that used Likert Scale questions to establishing measureable values from the respondent. The data analysis intends to determines whether there are significant effect between independent variables (Perceived Intergenerational Supportive Climate, Perceived Top Management Support, Perceived Organizational Institution Support) with dependent variable (Intergenerational Knowledge Transfer). The data was being analyzed using SPSS. Thus, this study has found that two independent variables which is Perceived Intergenerational Supportive Climate and Perceived Top Management Support has significant effect while one independent variable which is Perceived Organizational Institution Support has no insignificant effect with dependent variable (Intergenerational Knowledge Transfer).